A Preliminary Investigation of Lapis Judaicus as a Natural Anti-Nephrolithic Agent: Physicochemical Characterization and Pilot In Vivo Study in Albino Mice - Awatf Abadi, Malak Eljafari; Heba Kashker; Asma Almijrab; Laila Ferrara (AlQalam Journal of Medical and Applied Sciences, 2026)
Kidney stones represent a significant global health burden, with calcium oxalate stones accounting for approximately 80% of all cases. Traditional medicine systems have long utilized natural remedies for urolithiasis management, among which Lapis Judaicus (Hajar al-Yahood) holds a prominent position in Unani and Middle Eastern medicine. This preliminary experimental study investigated the litholytic potential of Lapis Judaicus using two distinct natural vehicles: lemon juice and yogurt. Four groups of male albino mice were employed: one healthy control, one nephrolithiasis group induced by calcium oxalate (80 mg/kg) over four consecutive days, and two treatment groups orally administered Lapis Judaicus (250 mg/kg) suspended in either lemon juice or yogurt for six days. Histopathological examination revealed complete dissolution of kidney stones and restoration of normal renal architecture in the mice treated with Lapis Judaicus in lemon juice, whereas the yogurt-treated group showed partial improvement with a noticeable reduction in stone size and number. Interestingly, although prior solubility tests indicated superior dissolution of Lapis Judaicus under acidic conditions (49.83% at pH 3.0), the acidic lemon juice vehicle demonstrated remarkable in vivo efficacy, suggesting the involvement of additional biological or chemical synergistic factors. These findings provide preliminary support for the traditional use of Lapis Judaicus in kidney stone management and highlight the potential of citrus-based delivery systems to enhance its litholytic activity. Further comprehensive studies are crucial to elucidate the precise mechanisms of action, optimize therapeutic dosing regimens, and establish safety profiles for potential clinical applications.